2004
DOI: 10.1892/0891-6640(2004)18<104:eoslos>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Supplemental Lactoferrin on Serum Lactoferrin and IgG Concentrations and Neutrophil Oxidative Metabolism in Holstein Calves

Abstract: Lactoferrin (LF) is an iron-binding protein present in both colostrum and secondary granules of polymorphonuclear neutrophils (PMNs). We hypothesized that supplemental LF enhances neutrophil function in neonatal calves. Newborn calves were assigned to receive colostrum (C), colostrum LF (CLF, 1 g/kg), or milk replacer LF (MRLF, 1 g/kg). Serum (LF and IgG) and whole blood (neutrophil isolation) samples were obtained prior to treatment (day 0) and at 24 hours and 9 days of age. Serum IgG concentrations (mean SD)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…11 The results of the study reported herein also indicate that the concentration of lactoferrin in equine colostrum varies considerably with a mean concentration of 21.7 mg/ml. Although it cannot be definitively stated that the higher serum lactoferrin concentrations in 1-3-day-old healthy foals, as compared to serum lactoferrin concentrations before ingestion of colostrum, were the result of transfer of maternal colostral lactoferrin, the timing of the increase and the significant correlation between serum lactoferrin and IgG concentrations in these foals are evidence of this event.…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…11 The results of the study reported herein also indicate that the concentration of lactoferrin in equine colostrum varies considerably with a mean concentration of 21.7 mg/ml. Although it cannot be definitively stated that the higher serum lactoferrin concentrations in 1-3-day-old healthy foals, as compared to serum lactoferrin concentrations before ingestion of colostrum, were the result of transfer of maternal colostral lactoferrin, the timing of the increase and the significant correlation between serum lactoferrin and IgG concentrations in these foals are evidence of this event.…”
Section: Discussionsupporting
confidence: 59%
“…10 In a separate study, 1-day-old calves had greater serum lactoferrin concentrations (1,565 6 1,114 ng/ml, SD) compared to presuckle values (324 6 334 ng/ml), though statistical comparison of these values was not provided. 11 However in this latter study, additional supplementation of colostrum or milk replacer with lactoferrin resulted in significantly greater increases in serum lactoferrin, compared to calves that received colostrum alone. 11 These results indicate that, at least in calves, the intestinal tract is capable of absorbing lactoferrin.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…It was seen that the specific growth rates were unaffected by the dietary treatments. It has been reported that dietary Lf regulates hydroxyl radical production by mammalian macrophages, granulocytes and neutrophil leucocytes [15,47] but does not alter granulocyte superoxide production in Holstein calves [55]. In fish, no effect on non-specific immunity after 19 days of Lf administration in Atlantic salmon was observed [23] while rainbow trout specimens orally treated with bovine Lf showed enhanced phagocytic activities and superoxide anion production by macrophages [17,19].…”
Section: Discussionmentioning
confidence: 98%